PRISON LAND UTILIZATION STRATEGY IN SUPPORTING THE DEVELOPMENT OF INDEPENDENCE FOR PRISONERS IN CLASS IIA BENGKULU PRISON - Ahmad Akbar Beng Lieng; Markus Marselinus Soge (Universitas Nusa Cendana, 2026)
This study examines the optimization of inmate development programs at Lapas Kelas IIA Bengkulu, focusing on the utilization of available land to support independence training. Although the institution has a large area of land with significant potential, its use has not yet been maximized. Using a descriptive qualitative approach, data were collected through interviews, observations, and document studies. The analysis is based on Mintzberg’s strategy theory and the concept of correctional development (SPPN). The findings show that the strategies implemented include agricultural activities, plantations, and land-based skills training aimed at supporting inmates’ independence and accelerating their social reintegration. However, the implementation of these strategies faces several challenges, such as unfavorable land conditions, limited facilities and skilled personnel, budget constraints, rigid institutional regulations, limited market access, and negative public stigma toward inmates and their products. Therefore, more comprehensive support, improved resource management, and stronger collaboration with external parties are needed to optimize land utilization and enhance the effectiveness of independence development programs. Keywords: Independence Development; Land Utilization; Prisoners